The notions of creativity and meta-operativity in Emilio Garroni. Recent interpretations in the Italian aesthetic debate on technology - Manera, Lorenzo (Aesthetica Preprint, 2022)
This contribution addresses Garroni’s notions of creativity and meta-operativity on three levels, exploring recent interpretations and relationships with contemporary aesthetic reflections about technology. Firstly, the paper discusses how Garroni (1976, 1977, 1978) developed a reflection focused on aspects of creativity and meta-operativity of human behaviour by drawing on Kant’s Third Critique. His conception of creativity refers to a form of ‘productive imagination’, a meta-operative process which allows us to deal with novelties by creating new rules and developing a dynamic relationship between creativity and legality. Secondly, the paper explores how the Italian philosopher (1986) foresaw the possibility of establishing meaningful forms of relationships with reality by analyzing the concept of experience, which allowed Aesthetic experience to be considered as a way of renewing the agency and the heuristic potential of creativity, intended as the main characteristic that defines the human behaviour. Thirdly, this contribution explores how, by drawing on an understanding of aesthetics intended not as a ‘philosophy of art’ but, in a broader sense, as a ‘non-special philosophy’, the author (2005) developed a comprehensive reflection on the concept of perception that has led to the development of the concept of meta-operativity. Finally, this contribution discusses how the latter was reinterpreted in contemporary aesthetic reflections on perceptual aspects that define our relationship with technological devices.